In situ synthesis of gold nanoparticles in polymer films under concentrated sunlight: control of nanoparticle size and shape with solar flux. Issue 2 (24th December 2019) - Nadal, E.; Barros, N.; Peres, L.; Goetz, V.; Respaud, M.; Soulantica, K.; Kachachi, H.
Abstract : We proposed a one step, green and efficient approach to synthesize plasmonic nanocomposites over large surfaces and with controlled morphologies. Abstract : We propose an original technique for synthesizing plasmonic nanocomposites under concentrated sunlight. Polymer films doped with gold salts are prepared by spin-coating; the nanoparticle growth is triggered within the polymer matrix by exposing the film to concentrated solar irradiation. For the first time, we demonstrate that the variation of solar flux alone allows for controlling the nanoparticle size distribution and shape and, thereby, the final plasmonic response of the composite. Interestingly, thanks to this optical approach, the in operando measurement of the spectroscopic response permits monitoring of the growth of the nanoparticles in real time. The experimental results give us details about the differences in the nanoparticle growth mechanisms at different solar fluxes. At high flux, small nanospheres with a diameter centered around 3 nm to 6 nm are formed. At lower flux, bigger nanoprisms of 12–18 nm are synthesized. The mechanisms are discussed and different pathways are envisaged. Finally, we demonstrate the possibility of performing a fully green synthesis by using our method to grow gold nanoparticles in a biopolymer.